Extensive Primary Orbital Malignant Melanoma Associated with Nevus of Ota - Mutmainah Mutmainah; Neni Anggraini; Evelina Kodrat (Majalah Oftalmologi Indonesia, 2021)
Primary orbital malignant melanoma is an extremely rare condition to present alone without previous extension of choroidal or conjunctival involvement. We reported the first case of malignant orbital melanoma without ocular involvement in a patient with nevus of Ota. A 52-year-old man presented with left proptosis and extensive bluish black pigmentation on left side of the face classified as Tanino type II of nevus of Ota and left ocular melanocytosis from birth. CT scan imaging showed extensive orbital mass occupying most of the orbital space. Transconjunctival biopsy was performed and a very pigmented mass was discovered, confirming the histopathology result of malignant melanoma. The patient was given up to five cycles of chemotherapy regimen. On serial orbital CT Scan, 33% of the tumor mass has disappeared after completing three cycles.